Factors associated with home birth in rural population during the first year of the COVID-19 pandemic in Peru. - Apolaya-Segura, Moisés (2024)
Introduction: Maternal mortality is a public health issue, with greater significance in rural populations. Home delivery (HD) persists at high rates in rural areas, increasing the risk of obstetric complications, hence the need to study the involved factors.Objective: To determine the factors associated with HD in the rural population of Peru. Methodology: A cross-sectional analytical study was conducted on women of childbearing age in rural areas using the 2020 Peruvian National Demographic and Family Health Survey (ENDES). Home delivery (HD) was defined as childbirth occurring within a residence with the assistance of institutional healthcare personnel or midwives. Weighted absolute and relative frequencies were obtained for complex sample calculations using Stata 16.0, along with crude and adjusted prevalence ratios. Results: A total of 5334 rural women were evaluated, with a mean age of 30.02 ± 7.35 years. Secondary education was reported by 46.84%, while 8.06% were illiterate. Additionally, 31.92% reported a language other than Spanish, and the frequency of home delivery was 16.76%. In adjusted multivariate analysis, factors associated with HD included: speaking a different language (aPR 2.27, 95% CI 1.13-4.56, p=0.021), residing in a city above 1000 meters above sea level (aPR 1.79, 95% CI 1.33-2.40, p<0.001), lower wealth index compared to the poorest (aPR 0.31, 95% CI 0.16-0.60, p=0.001), having access to electricity (aPR 0.53, 95% CI 0.37-0.76, p=0.001), and receiving prenatal care from an obstetrician (aPR 0.65, 95% CI 0.49-0.86, p<0.001). Conclusions: The frequency of HD in the rural population during the pandemic in Peru was high. Factors increasing HD included language diversity and residing at higher altitudes, while factors decreasing HD included wealth index, access to electricity, and obstetrician-led prenatal care.